Making Ripples: Rethinking Pedagogy in the Digital Age. (December 2013) - Paranandi, Murali
This essay presents a pedagogical model for beginning design that introduces digital fabrication methods through an integrated learning framework. Ripples - a wall sculpture made collectively by all second year architecture and interior design students as a joint project between studio, graphics and shop—exemplifies design practice as a collective activity. In this example, solutions emerge out of interactions among multiple stakeholders through iterative experimentation and optimization. The goal of this essay is to provoke a rethinking of the status-quo pedagogical practices in order to incorporate digital fabrication within existing curricular structures as a core skill for beginning design students, rather than merely as a technology course elected by a few students. Conclusions suggest the relevance to broader contexts of lessons learned from this modest experiment.